The validity of award criteria that incentivize salary increases in public sector contracts. Commentary following the CJEU judgment of 5 March 2026 (C-210/24) and the Basque Country’s ROARC 75/2026 of 22 April - Sánchez Ocaña, José Miguel (LABOS Revista de Derecho del Trabajo y Protección Social, 2026)
Social clauses in public sector contracts have been only sparsely addressed by the Court of Justice of the European Union (CJEU) over the past decade. The current generation of directives, more conducive to socially responsible public procurement than its predecessor, has coexisted with a limited and ambiguous body of European case law, in some instances grounded in repealed legislative frameworks. On this occasion, the CJEU delivered its ruling in the judgment of 5 March 2026, following a request for a preliminary ruling referred by the Basque Administrative Tribunal for Public Procurement Appeals. In its judgment, the Court upheld, in abstract terms, a social clause framed as an award criterion that assessed wage increases for workers above the amount established in the applicable sectoral collective agreement. This commentary analyses both the CJEU judgment and the subsequent decision adopted by the referring administrative body, drawing on previous and contrasting judicial and administrative doctrines in order to understand the implications of this ruling for the future of labour-related social clauses.